2
$\begingroup$

There's a problem in a book regarding exact differential equation :
Solve : $$x\,dx+y\,dy = \frac{a^2(x\,dy-y\,dx)}{x^2+y^2}$$ The author further proceeds to rearrange above in the form $M\,dx+N\,dy=0$ where $$M=x+\frac{a^2y}{x^2+y^2} ; N= y-\frac{a^2x}{x^2+y^2}$$ Which further implies $$M_y=N_x=\frac{a^2(x^2-y^2)}{(x^2+y^2)^2}$$ This is the required condition for the given equation to be exact and the solution is obtained using standard formula.

But, what I did is as follows : $$x\,dx+y\,dy = \frac{a^2(x\,dy-y\,dx)}{x^2+y^2}$$ $$\to (x^2+y^2)x\,dx + (x^2+y^2)y\,dy=a^2(x\,dy -y\,dx)$$ Therefore $$(x^3+xy^2+a^2y)\,dx + (y^3+yx^2-a^2x)\,dy =0$$ Comparing it with the equation $M\,dx+N\,dy=0$ we get, $$M=x^3+xy^2+a^2y; N=y^3+yx^2-a^2x$$ But $$M_y=2xy+a^2; N_x=2xy-a^2$$ Evidently, $M_y\neq N_x$.
So what am I doing wrong here?
At first I thought I shouldn't/couldn't just simply multiply both sides of the given equation with the denominator ($x^2+y^2$) of right hand side if it's zero, but since as it's already in denominator isn't it understood that it isn't/can't be zero ??
Any help is really appreciated.

$\endgroup$
1

2 Answers 2

4
$\begingroup$

$$x\,dx+y\,dy = \frac{a^2(x\,dy-y\,dx)}{x^2+y^2}\tag 1$$ As you correctly found : Equation $(1)$ is an exact ODE.

You transformed Eq.$(1)$ into Eq.$(2)$: $$(x^3+xy^2+a^2y)\,dx + (y^3+yx^2-a^2x)\,dy =0\tag 2$$

Again you correctly found : Equation $(2)$ is not an exact ODE.

This is not contradictory because Eqs.$(1)$ and $(2)$ are not the same ODE.

In order to transform Eq.$(2)$ into an exact ODE one have to multiply it with an "integration factor", say $\mu(x,y)$.

One find that $\mu(x,y)=\frac{1}{x^2+y^2}$. $$\mu(x,y)\Big( (x^3+xy^2+a^2y)\,dx + (y^3+yx^2-a^2x)\,dy\Big) =0\tag 3$$ $$ \frac{x^3+xy^2+a^2y}{x^2+y^2}\,dx + \frac{y^3+yx^2-a^2x}{x^2+y^2}\,dy =0\quad\text{is exact.}$$ In fact Eq.$(3)$ is equivalent to Eq.$(1)$ thanks to the correct $\mu(x,y)$.

$\endgroup$
0
2
$\begingroup$

In my mind, your question is about integrating factor.

You have checked your equation $$ (x^3+xy^2+a^2y)dx+(y^3+yx^2-a^2x)dy=0 $$ is not exact.

That's why we need integrating factor. Here the integrating factor is exactly $\frac{1}{x^2+y^2}$.

By the integrating factor, we make your equation an exact equation deliberately, then we can solve the ODE by exact equations.

If $x^2+y^2=0$, then this ODE is not $\textbf{well-defined}$.

p.s. It's my first time to answer a problem. Perhaps I misunderstand your problem, please tell me and I would try to correct my answer.

$\endgroup$
1
  • 2
    $\begingroup$ As it’s currently written, your answer is unclear. Please edit to add additional details that will help others understand how this addresses the question asked. You can find more information on how to write good answers in the help center. $\endgroup$
    – Community Bot
    Jan 21 at 14:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.